2018
DOI: 10.4103/ijo.ijo_688_17
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral disciform keratitis of presumed adenoviral etiology

Abstract: Adenoviral conjunctivitis may lead to subepithelial corneal infiltrates as a late complication. Herein, we aim to present a 19-year-old healthy female, who developed bilateral disciform keratitis three weeks after suffering adenoviral conjunctivitis. She presented with widespread subepithelial corneal infiltrates in addition to central corneal edema with white distinct border resembling immune stromal ring, as well as Descemet's folds and keratic precipitates in the central area. Following topical corticostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…A recent study has reported that the levels of inflammatory factors, such as G-CSF, TNF-α, IL-6, and IP-10, are significantly higher in severely ill COVID-19 patients than those in less severely ill patients, indicating that cytokine surge is involved in the pathogenesis of the disease [12]. In infectious immune corneal injuries, bilateral peripheral ulcerative keratitis caused by the herpes simplex virus [19] and bilateral disciform keratitis complicated by adenoviral conjunctivitis [20] due to the induction of inflammatory reactions or immunological responses in the corneal stroma by immune-degrading complexes have also been reported. However, these delayed corneal infiltrations display different clinical signs, and therefore, they are often misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that the levels of inflammatory factors, such as G-CSF, TNF-α, IL-6, and IP-10, are significantly higher in severely ill COVID-19 patients than those in less severely ill patients, indicating that cytokine surge is involved in the pathogenesis of the disease [12]. In infectious immune corneal injuries, bilateral peripheral ulcerative keratitis caused by the herpes simplex virus [19] and bilateral disciform keratitis complicated by adenoviral conjunctivitis [20] due to the induction of inflammatory reactions or immunological responses in the corneal stroma by immune-degrading complexes have also been reported. However, these delayed corneal infiltrations display different clinical signs, and therefore, they are often misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Rings in that case are associated with widespread subepithelial corneal infiltrates. They resolve upon topical treatment with prednisolone acetate [ 56 ].…”
Section: Infectious Causes Of Corneal Ring Infiltratementioning
confidence: 99%